Patient-centric decision framework for treatment alterations in patients with Chemotherapy-induced Peripheral Neuropathy (CIPN). (September 2021) - Hertz, Daniel L.; Childs, Daniel S.; Park, Susanna B.; Faithfull, Sara; Ke, Yu; Ali, Nadeen T.; McGlown, Sheila Marie; Chan, Alexandre; Grech, Lisa B.; Loprinzi, Charles L.; Ruddy, Kathryn J.; Lustberg, Maryam
Highlights: Treatment alteration is recommended for chemotherapy-induced neuropathy (CIPN). Treatment alterations for CIPN is common in clinical care but is not evidence-based. Benefits of treatment alteration include reducing CIPN severity and persistence. Risks of treatment alteration include reducing treatment response and survival. Patient preferences and treatment goals should be considered when altering treatment. Abstract: Recently updated American Society of Clinical Oncology (ASCO) guidelines for Prevention and Management of Chemotherapy-Induced Peripheral Neuropathy (CIPN) in Survivors of Adult Cancers make a single recommendation to alter treatment by delaying, decreasing, or discontinuing dosing in patients who develop CIPN during neurotoxic chemotherapy treatment. Dosing guidelines have inconsistent recommendations for when (i.e., what CIPN severity) and how (i.e., delay, decrease, or discontinue) to alter neurotoxic chemotherapy treatment in patients with CIPN. Clinical decision making requires an understanding the benefits and risks of treatment alteration, in addition to consideration of other disease and patient factors. This review summarizes four areas of literature and culminates in a patient-centric decision framework to guide clinicians in helping patients to make treatment alteration decisions. First, we describe the current practice of altering treatment due to CIPN, including treatment alteration recommendations and published rates. Second, we summarize the potential benefits of treatment alteration including the reduction in CIPN severity and persistence. Third, we evaluate the potential risk of treatment alteration in compromising treatment efficacy by reviewing prospective trials comparing dosing regimens and retrospective analyses of the effect of relative dose intensity on efficacy. Fourth, we summarize disease and patient factors that should be considered when making a treatment alteration decision for a patient. We then propose a patient-centric decision framework that clinicians can use to assess an individual patient's current and anticipated future CIPN severity and compare that to their maximum tolerable severity to determine whether they should continue, delay, decrease, or discontinue neurotoxic chemotherapy.